Utilização do YouTube no ensino e aprendizagem de Libras: formação voltada para tradutores e intérpretes - Duarte, Lívia Alves (2023)
This research seeks to understand how and if YouTube is being used in the teaching and learning of Brazilian Sign Language (Libras) in the education of translators and interpreters of Libras-Portuguese, specifically, the one offered in the state of Goiás. Two institutions are part of this research: the Universidade Federal de Goiás (UFG), which offers an undergraduate course in Languages: Translation and Interpretation in Libras/Portuguese (BA), and the Centro de Capacitação de Profissionais da Educação e Atendimento às Pessoas com Surdez de Goiânia (CAS-Goiânia), which offers continuing education courses. The research problem is: from the perspective of teachers, students and graduates of these courses, is YouTube being used in the learning and development of Libras in the education of translators and interpreters of Libras-Portuguese? In search of answers to the problem presented, the general objective was set as follows: to analyze whether YouTube is being used in the learning and development of Libras in the education of translators and interpreters of Libras into Portuguese from the perspective of teachers, students and graduates of the courses of the institutions in question. The research uses a qualitative methodological approach of exploratory and descriptive nature (GIL, 2008). The data were collected through a questionnaire with open and closed questions, and then organized by means of categorization and description (GIL, 2008), using the content analysis technique (BARDIN, 2002). The results indicated that the use of YouTube in the teaching of Libras for education and interpreters of the Libras-Portuguese language pair already occurs, sometimes as the main focus of the exposure of content, but mainly as support material inside and outside the classroom. It is expected that the results will contribute positively to future research in the education offered for translators and interpreters of Libras into Portuguese in Brazil.